2018
DOI: 10.1007/s00436-017-5734-1
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Cryptosporidium parvum subtype and Enterocytozoon bieneusi genotypes in dromedary camels in Algeria

Abstract: Little information is available on the occurrence of the zoonotic protists Cryptosporidium spp. and none on Enterocytozoon bieneusi in camels. This preliminary study was conducted to examine the identity of Cryptosporidium subtypes and E. bieneusi genotypes in dromedary camels in Algeria. A total of 39 fecal specimens were collected from young camels. PCR-sequence analysis of the small subunit rRNA was used to detect and genotype Cryptosporidium spp. Cryptosporidium parvum present was further subtyped by seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
3
19
2
Order By: Relevance
“…Of the 12 C. parvum isolates, 5 were identified as subtype IIdA19G1 (n = 4) or subtype IIdA15G1 (n = 1) based on sequencing analysis of the gp60 gene, and these 2 subtypes have also frequently been found in bovines [31]. In addition, subtypes IIdA19G1 and IIdA15G1 have also been detected in ruminants (sheep, goats, deer), alpacas, horses, rodents (mice, hamsters, squirrels), pigs, carnivores (dogs, gray wolves, raccoon dogs), and in wastewater around the world [3,19]. Meanwhile, previous reports have shown that subtypes IIdA15G1 and IIdA19G1 can also cause human infections [13,30].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 C. parvum isolates, 5 were identified as subtype IIdA19G1 (n = 4) or subtype IIdA15G1 (n = 1) based on sequencing analysis of the gp60 gene, and these 2 subtypes have also frequently been found in bovines [31]. In addition, subtypes IIdA19G1 and IIdA15G1 have also been detected in ruminants (sheep, goats, deer), alpacas, horses, rodents (mice, hamsters, squirrels), pigs, carnivores (dogs, gray wolves, raccoon dogs), and in wastewater around the world [3,19]. Meanwhile, previous reports have shown that subtypes IIdA15G1 and IIdA19G1 can also cause human infections [13,30].…”
Section: Discussionmentioning
confidence: 99%
“…[ 14 , 15 ]. Notwithstanding, little is available on the gastrointestinal parasitic infections in dromedary camels in Algeria [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although Cryptosporidium spp. from cattle, horses, camels and chickens have been recently characterized using molecular biological tools [ 20 23 ], little information is available on the identity of Cryptosporidium spp. in goats and sheep.…”
Section: Introductionmentioning
confidence: 99%